A Juggler on the Moon: How Sounds Think in Tom Stoppard's Darkside - Verma, Neil (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2016)
This essay explores Tom Stoppard’s 2013 radio play Darkside, which incorporates elements of Pink Floyd’s 1973 album TheDark Side of the Moon, and dramatizes a series of thought experiments. I show how the combination of these three forms necessitates a rethinking of how sounds operate in radio drama, chart the play’s habits of diversion and evasion, and discuss how these tendencies are brought to bear on the central theme of climate change. At the heart of this essay is a proposal that the idea of the “sound of thought” embodied in Darkside may prompt a new approach to the theory of radio, one that begins not with what sounds mean, but with how sounds “think”.